A STUDY OF IDENTIFYING AND DISCUSSING CLOUD COM PUTER THREATS AND ATTACKS WITH MITIGATION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Saving documents by the use of the cloud is identified as fast and expanding modern technology that helps in cooperating numerous internet activities to the customers. Additionally, it is incorporated in big companies such as Amazon, Apple, Google, Microsoft, and IBM. However, these companies have reported a great loss in their data due to malicious invaders, hackers, and many other unauthorized users as it al- lows third-party involvement. Therefore, the companies need to upgrade and maintain their positions in the fast computer-based environment and it’s had to enhance services of large number of users. The fast-growing technology has raised needs that need to be addressed with security which hinders its work. Challenges in the security sectors such as threats and attacks have greater concerns that need to be addressed properly in avoiding security problems for better customer services. The paper identifies the use of internet storage, the obstacles, and insecurity plots with their immediate methods that can be used even in the future.